Study of the Prevalence of Glaucoma in Kazakhstan - Tashtitova, Lyailya; Aldasheva, Neilya (Klinische Monatsblätter für Augenheilkunde, 2021)
Background Glaucoma is one of the leading causes of permanent visual disability around the world. However, the available literature lacks data on the prevalence of glaucoma in Central Asia, particularly in the Republic of Kazakhstan.Objective The study was aimed at assessing the prevalence of glaucoma in the population of the Republic of Kazakhstan over 40 years old in 2019.Methods A retrospective study was based on the analysis of the results of glaucoma screenings in 171 832 patients over 40 years old living in Kazakhstan (in 14 counties). Glaucoma cases were confirmed by Goldmann tonometry, fundus photography, and visual field testing. Demographic indicators, territorial differences, and hereditary predisposition were studied and analysed. In addition, blood pressure was measured.Results Of 171 832 patients examined, 452 with verified glaucoma were identified. The average age of the patients was 63.9 ± 9.4. In rural areas, the prevalence of glaucoma was higher compared to the urban population. The overall prevalence of glaucoma among people over 40 years old was 2.37 ± 0.17. The prevalence of glaucoma among women was higher than for men, with an indicator of 1.91 (95% CI relative risk 1.78 – 2.03) (p < 0.05). The highest prevalence was found in the 71 – 75 age group [equals to 14.2% (95% CI 11.7 – 19.9)], with a statistically significant difference (p < 0.05). The highest prevalence of glaucoma was observed in the group of people with a hereditary predisposition, with an indicator of 14.7% (95% CI 0.6 – 1.9) (p < 0.05). Among all patients with concomitant arterial hypertension (n = 90, 19.9%), women (60%) compared with men (40%) had a 2.4% higher risk of glaucoma morbidity (95% CI 1.2% − 3.8%).Conclusion This study provides updated information on the prevalence of glaucoma in Kazakhstan. The results obtained confirm that the increase in the prevalence of glaucoma in Kazakhstan is directly proportional to the increase in the patientsʼ age. These results showed the importance of screening for a timely diagnosis, especially for patients with high risk factors such as hereditary predisposition. Moreover, the results indicate that the early detection of systemic hypertension and increased intraocular pressure can be used for the prevention of undesirable outcomes such as an irreversible blindness.
Keywords: epidemiology; glaucoma; prevalence; screening